Performance of a new short‐type double‐balloon endoscope with advanced force transmission and adaptive bending for pancreaticobiliary intervention in patients with surgically altered anatomy: A propensity‐matched analysis. Issue 1 (3rd October 2018) - Yamada, Atsuo; Kogure, Hirofumi; Nakai, Yousuke; Takahara, Naminatsu; Mizuno, Suguru; Tada, Minoru; Koike, Kazuhiko
Abstract : Background and Aim: A new short‐type double‐balloon endoscope (DBE) has been developed with a major focus on facilitating scope insertion to the target site for pancreaticobiliary interventions in patients with surgically altered anatomy. We investigated the performance of this new short‐type DBE by comparing it with a conventional DBE. Methods: Data from 885 endoscopic retrograde cholangiopancreatography (ERCP) procedures using balloon endoscopy were analyzed. We used propensity score matching to adjust for differences between patients who underwent ERCP procedures using the new short‐type DBE versus the conventional short‐type DBE. Results: A total of 163 pairs of patients were selected by propensity score matching. Success rate of reaching the target site was 100% in both the new DBE group and the conventional DBE group ( P = 1.0). The new DBE group had a shorter insertion time required to reach the target site than the conventional DBE group (10 min vs. 14 min, P < 0.01). Success rate of pancreaticobiliary interventions in the new DBE group was as high as that in the conventional DBE group (92% vs. 89% P = 0.35). Overall procedure time decreased from 62 min in the conventional DBE group to 55 min in the new DBE group ( P = 0.26). No significant differences in the rates of adverse events were observed between the two groups. Conclusion: A new short‐type DBE allows faster insertion to the target site for pancreaticobiliary intervention in patients with surgically altered anatomy.